2018
DOI: 10.1186/s12916-018-1018-6
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of clinical research in critical care: a scoping review

Abstract: BackgroundThe ability to reproduce experiments is a defining principle of science. Reproducibility of clinical research has received relatively little scientific attention. However, it is important as it may inform clinical practice, research agendas, and the design of future studies.MethodsWe used scoping review methods to examine reproducibility within a cohort of randomized trials examining clinical critical care research and published in the top general medical and critical care journals. To identify relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 47 publications
1
48
0
Order By: Relevance
“…Another study compared the results from a limited number of initial clinical studies and respective follow-up studies. It concluded that less than 50% of the investigated studies reported reproducible effects [49]. However, it is not clear how representative the data are.…”
Section: Resultsmentioning
confidence: 99%
“…Another study compared the results from a limited number of initial clinical studies and respective follow-up studies. It concluded that less than 50% of the investigated studies reported reproducible effects [49]. However, it is not clear how representative the data are.…”
Section: Resultsmentioning
confidence: 99%
“…Precision medicine improves patient diagnoses and treatments by integrating clinical and biomarker data, which requires effective data management for reproducibility of clinical research findings (Vargas and Harris, 2016; Leopold and Loscalzo, 2018; Niven et al , 2018). The studies often span institutions, departments, and research teams, where patient data is collected and processed in a specialized way.…”
Section: Introductionmentioning
confidence: 99%
“…A recent scoping review of the reproducibility of research in critical care found that less than half of critical care practices had reproducible effects, and worse, two practices that were initially efficacious were found to be harmful in repeated studies (Niven et al., ), a major reason why it is so important to conduct replication research. Further, the challenges of reproducibility in research are not limited to the United States.…”
mentioning
confidence: 99%